Eva y crisis financiera mundial - Pacheco Mexzon, Raimundo Renaun (2013)
From the year 2,008 which starts in the United States of America financial crisis, to date, 2,013 year June has taken alarming proportions worldwide affecting not only the economic but also the social and business. In this framework we wonder what would happen to economic value creation of a company to keep this situation. To our knowledge the company would be affected can destroy rather than create economic value.